The pilot area development programme - Scully, John J. (Statistical and Social Inquiry Society of Ireland, 1968)
In 1961, the Minister for Agriculture set up an informal committee which included representatives of the Departments of Agriculture, Finance, Gaeltacht and Lands, the Central Statistics Office, and An Foras Taluntais "to consider and report on sound and practicable measures to deal with special problems of agriculture" in the West. This committee subsequently made a number of specific suggestions regarding possible solutions to the problem.
Read before the Society, 26 January 1968
Keywords: Regional development; Irish agriculture; Pilot area development programme; 314.15